A biocompatible polyurethane fluorescent emulsion with aggregation-induced emission for targeted tumor imaging. Issue 10 (17th February 2023) - Ou, Yangcen; Wang, Xiaofei; He, Nan; Wang, Xiao; Lu, Dan; Li, Zhen; Luo, Feng; Li, Jiehua; Tan, Hong
Abstract : A biocompatible fluorescent emulsion with targeting ability was successfully prepared via introducing TPE and phenylboronic acid into polyurethane, and can be used for tumor cell imaging. Abstract : The applications of fluorescence imaging in tumor detection and assistance in tumor resection have become progressively more widespread. Biocompatible fluorescent nanoparticles with high sensitivity and selectivity are a challenge for biological fluorescence imaging. Ligand-mediated targeting of nanoparticles to tumors is an appealing tactic for improving imaging efficiency. Herein, tetraphenyl ethylene (TPE) and phenylboronic acid (PBA) were introduced into polyurethane to synthesize a PU–TPE–PBA (PTP) fluorescent emulsion with aggregation-induced emission (AIE) for targeted tumor imaging. The PTP emulsion with a size of less than 50 nm shows excellent stability and high fluorescence sensitivity (extremely low TPE concentrations of 0.31 μg mL −1 ). Since PBA can selectively recognize and bind to sialic acid (SA) which is widely overexpressed in tumor cells, such PTP nanoparticles can be enriched in tumors and retained for longer periods due to enhanced permeability and retention (EPR) as well as active targeting effects. In addition, the PTP emulsion exhibits good biocompatibility and biosafety. Therefore, the novel PTP emulsion is promising for tumor cell imaging.